General combinative ability of parental lines of watermelon in terms of yield and dry matter content - E. A. Varivoda; N. G. Baybakova; G. V. Varivoda (Овощи России, 2020)
Relevance. The creation of heterotic hybrids of watermelon is one of the modern breeding trends for solving the problem of providing the population of the Russian Federation with melon production. The process of creating heterosis hybrids can be accelerated by the assessment of the total combination ability (ОCS) of parental lines.Materials and methods. The studies were carried out in the zone of the Volgograd Trans-Volga region at the Bykovskaya melon selection experimental station, in dry conditions in 2018 and 2019. The object of research was 9 paternal lines and 3 maternal lines of watermelon. The assessment of the general combining ability was carried out according to two indicators: yield and dry matter content.Results. In the course of the research, the obtained F1 watermelon hybrids were assessed for a set of economic characteristics in comparison with the standards: Zenit, Sinchevsky and Barkhan. Based on the results of the work, F1 hybrids were identified according to the length of the growing season, yield, and dry matter content. By selecting valuable genetic sources with a high GCS, it is possible to successfully conduct breeding to improve the economically valuable indicators of F1 watermelon hybrids. According to the results of studies on yield, both in 2018 and in 2019, heterotic hybrids were distinguished, obtained from crossing with the paternal lines Favorit, Stimul, Ikar, the average effect over two years ranged from 3.5-10.6 t/ha. Among the studied maternal lines, the line Chms-4 has a positive effect, the average effect was 1.2 t/ha. In terms of dry matter content, a positive effect was found in the paternal lines Stimul – 1.8%, Medunok – 1.6%, Favorit – 0.8%, and in the maternal line Chms – 41.8%Conclusions. Based on the results of the analysis of the combining ability in terms of yield and dry matter content, we identified two promising paternal lines for creating heterotic watermelon hybrids: Favorite, Stimul. Also, one maternal line Chms-4 was distinguished. When using these lines in heterotic breeding of watermelon, in most crossing combinations, heterosis will be manifested in one or two characters.